2011
DOI: 10.1017/s1751731110002041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofuel co-products in pig diets on the excretory patterns of N and C and on the subsequent ammonia and methane emissions from pig effluent

Abstract: This study was conducted to investigate the effects of incorporation into pig diets of 20% of different co-products from the biofuel industries, which are rich in fibre, on animal growth performance, on nitrogen (N) and carbon (C) excretions, and on the subsequent ammonia volatilisation and methane production during the storage of slurry. Five experimental diets mainly based on wheat and soyabean meal were formulated: two control diets, a control high-protein (CHP) diet with 17.5% of crude protein (CP) and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 22 publications
4
36
0
Order By: Relevance
“…The greater fibre content and the lower fat content of RSM compared to soybean meal implies the need for increasing added fat levels when RSM is used. Jarret et al (2011b) and McDonnell et al (2010) reported a greater fat digestibility and a lower aNDFom and ADFom digestibility when fatty RSM was included in finishing pig diets. In the present work statistical significant differences were observed for DM, OM and CP digestibility, but aNDFom and ADFom digestibility also tended to be lower when including 200 g/kg of RSM in finishing pig diets.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The greater fibre content and the lower fat content of RSM compared to soybean meal implies the need for increasing added fat levels when RSM is used. Jarret et al (2011b) and McDonnell et al (2010) reported a greater fat digestibility and a lower aNDFom and ADFom digestibility when fatty RSM was included in finishing pig diets. In the present work statistical significant differences were observed for DM, OM and CP digestibility, but aNDFom and ADFom digestibility also tended to be lower when including 200 g/kg of RSM in finishing pig diets.…”
Section: Discussionmentioning
confidence: 97%
“…In the present work statistical significant differences were observed for DM, OM and CP digestibility, but aNDFom and ADFom digestibility also tended to be lower when including 200 g/kg of RSM in finishing pig diets. It has been widely recognized that feedstuffs with high indigestible fibre might increase rate of passage and reduce its digestibility (Wenk, 2001;Sauvant et al, 2004;Jarret et al, 2011b). Additionally, some authors have reported that protein availability in by-products might be impaired because it is enclosed in the fibre fraction, limiting the accessibility of digestive enzymes that hydrolyse the protein (Bjergegaard et al, 1991;Gasa et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In manure, the CH 4 production is promoted by lack of oxygen, high temperature, high level of degradable OM, high moisture content, low redox potential, neutral pH and C/N ratio between 15 and 30 . According to the guidelines for National Greenhouse Gas Inventories (IPCC, 2006), CH 4 emissions from manure (CH 4, Manure , in m 3 ) can be estimated based on the amount of excreted OM, in kg; the ultimate CH 4 potential (B 0 ), in m 3 per kg OM; and the methane conversion factor (MCF), in percentage: In a study conducted on slurry samples from pigs fed diets with different fibre contents, B 0 values around 0.46 m 3 per kg OM were reported whatever the diet composition (Jarret et al, 2011a). In a similar experiment, extreme MCF values were observed, ranging from 1.3% to 85.4% according to manure type, manure management, storage duration and fibre content (Jarret et al, 2011b).…”
Section: Methanementioning
confidence: 99%